The Authenticity of Ideas, Public Organization Capacity, and Technological Innovation in the Implementation Model of Quality Public Service System in Indonesian Government Administration - Rifai Rifai; Firmansyah; Rahmad Hidayat; Haeril (Jurnal Studi Sosial dan Politik, 2024)
Public demand for quality and innovative public services has surged, requiring a strong response from government administration, especially in the era of decentralization. This study aims to explore the originality of ideas, the capacity of public organizations, and the role of technological innovation in improving the quality of public service systems in Indonesian government administration focusing on local governments, particularly in the area of licensing services. The methodology used involves a comprehensive analysis of factors affecting service quality, including implementation patterns, human resource support, and organizational and infrastructure capabilities. The research evaluates how these elements interact to form an integrated management system capable of meeting public expectations and examines the arrangements, mechanisms and implementation procedures of task forces, emphasizing their critical role in service improvement. The findings reveal that the government's ability to address various public service challenges significantly affects its credibility and support from the public, thus service quality should be a priority at all levels of government, from implementation to leadership. Local governments, should adopt an integrated management approach, with a particular focus on licensing services, to ensure efficiency and responsiveness. This research concludes that service quality is highly dependent on systematic policy implementation, human resource competence and support, and the adequacy of organizational facilities and infrastructure. The strategic organization, operational mechanisms and procedural framework of the task force are key in driving improvements in public service delivery, need for concerted efforts to foster innovation and capacity building in public organizations to meet society's growing demands for quality public services.